Microsatelite –based population structure corresponding to the geographic origin of saltwater crocodiles in Sarawak River Basins. - Reymathi, Nadarajan; Ruhana, Hassan; Mohd Izwan Zulaini, Abdul Gani; Azroie, Denel (Prince of Songkla University, Thailand, 2023)
Of the recognized 24 crocodilian species, two species are found in Sarawak: the saltwater crocodile (Crocodylus porosus) and Malayan false gharial (Tomistoma schlegelii). C. porosus is the most commonly found crocodile and currently listed in Appendix II of the Convention on International Trading in Endangered Species of Wild Flora and Fauna (CITES), which allows harvesting wild populations for commercial purposes. To strengthen conservation efforts, ecological and genetic data are needed to inform management decisions. Thus, this study was designed to estimate relationship coefficients between crocodiles in thirteen river basins using 13 microsatellite markers. Fifty-eight wild crocodile samples were obtained and finally analysed by clustering of PCR products. Of the 60 samples amplified, one marker (Cj35) was polymorphic and showed double bands, whereas the other seven markers (Cj127, Cj131, Cj122, Cj101, Cj119, CUD68 and Cj16) revealed a single band. Microsatellite loci (Cj105, Cj18, Cj104, Cp10, and Cu4-121) displayed multiple bands. Using the unweighted pair group with the arithmetic mean (UPGMA) clustering method, an unrooted phylogenetic tree was obtained, with coefficients ranging between 0.51 and 1.00. We successfully assessed population genetic structure and resolved genetic relationships among six clades (Clade A to F) out of the total seven clades. DNA microsatellites are a promising resource for determining the relationships among crocodiles in Sarawak. The findings are useful for future sustainable utilization of the wild crocodile population.